BUKU PANDUAN PENGKAFIRAN: Evaluasi Kritis Tibyān fī Ma’rifat al-Adyān karya Nūr al-Dīn al-Ranīrī - Ismail Fahmi Arrauf Nasution (Jurnal Theologia, 2018)
Abstract: The aim of this article is to critically evaluate the thought of Nūr al-Dīn al-Ranīrī, particularly his thought in Tibyān fī Ma’rifat al-Adyān. The book contained his accusation of others as being a kafir. This Indian origin theologian explained the history of religions from the times of Adam to the times of Jesus. He claimed that those pre-Islamic religion had perverted. He discussed also Islamic theological schools such as Rafidi, Khawarij, Jabbariyah, Qadariyah, Jahmiyah, Murji'ah and Karamiyah. He said that those schools are perverted as well. According to him, only Ahl al-Sunnah wa ’l-jamā’ah is the right theology. He also discussed various ideologies and the practices of mysticism that have ever grown and claimed that those are perverted too, except the akhlaqi tasawwuf. This article reviews the historical background of Aceh chronically till this "guidance book of takfir" come into existence. For that cause, the content of Tibyān fī Ma’rifat al-Adyānwill is discussed in brief. Finally, the theological thought of al-Ranīrī regarding the unity of being. The article focuses on the criticism over the attack of al-Ranīrī against the concept of the unity of being held by Hamzah Fansūrī and Shams al-Dīn al-Sumatranī.Abstrak: Tulisan ini bertujuan melakukan evaluasi kritis atas pemikiran Nūr al-Dīn al-Ranīrī, khususnya dalam bukunya Tibyān fī Ma’rifat al-Adyān. Dalam buku tersebut dia mengkafirkan banyak pihak. Teolog asal India itu mengulas sejarah agama-agama sejak Adam hingga Isa al-Masih. Dia mengatakan agama-agama tersebut telah menjadi agama yang sesat setelah Islam muncul. Selanjutnya dia membahas aliran-aliran teologi seperti Rafidi, Khawarij, Jabariyah, Qadariyah, Jamamiyah, Murji’ah dan Karamiyah. Dia mengatakan semua aliran teologi tersebut adalah sesat. Menurutnya aliran yang benar hanya Ahl al-Sunnah wa ’l-Jamā’ah. Selanjutnya dia mengulas berbagai itikad dan praktik mistisme yang pernah berkembang dan mengatakan semua itu sesat kecuali aliran tasawuf akhlaqi. Tulisan ini mengulas tentang latar belakang Aceh secara kronologis hingga “buku panduan pengkafiran” tersebut hadir. Selanjutnya diulas secara ringkan isi Tibyān fī Ma’rifat al-Adyān. Terakhir dilakukan evaluasi kritis atas pandangan teologis al-Ranīrī tentang Waḥdat al-Wujūd. Tulisan ini berfokus pada kritik atas serangan al-Ranīrī terhadap pemikiran Waḥdat al-Wujūd yang dipegang oleh Hamzah Fansūrī dan Shams al-Dīn al-Sumatranī.